Analisis Faktor-Faktor yang Menyebabkan Rendahnya Hasil Belajar Siswa di SD Negeri Karang Ringin 1 - Meliana Meliana; Adrianus Dedy; Robert Budilaksana (Journal on Education, 2023)
The purpose of this research is to identify the factors that cause low student learning outcomes. This research method is a qualitative research with the subject of 10 (ten) students identified as having difficulty learning mathematics. The technique used to collect data is observation through questionnaires, interviews and documentation. Data analysis was performed by data reduction, data presentation and conclusion. The conclusion of the results of this study is the type of learning difficulties experienced by students, namely difficulties in understanding concepts and difficulties in numeracy skills. Factors that cause students to experience learning difficulties are internal factors which include students' attitudes in learning, as well as students who do not have an interest in learning mathematics, and students' learning motivation is still low. While external factors include family factors, environmental factors and educator factors.